Seamless Textual Version Using with MarianMT Technique - B. Snehalatha; S. Noortaj (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This project presents a context-aware, multilingual translation system that enhances the accuracy and fluidity of translations for multiple Indian languages. The system combines MarianMT, a robust machine translation model, with BERT for contextual understanding, enabling more accurate translations by capturing the nuances of word relationships within each sentence. Fine-tuning the MarianMT model with an English-Hindi parallel corpus further improves the model’s sensitivity to linguistic subtleties, idiomatic expressions, and cultural references unique to Hindi. Efficiency is optimized through mixed-precision training and gradient accumulation, allowing the model to handle large datasets effectively while minimizing computational overhead. To extend functionality across Indian languages, the system incorporates models from the HelsinkiNLP OPUSMT series, accessed via the Hugging Face transformers library. This integration supports real-time translation for Hindi, Marathi, Telugu, Kannada, Tamil, Bengali, and Gujarati, bridging language barriers and enhancing communication. The system also includes speech-to-text and text-to-speech capabilities, powered by libraries like speech_recognition and gTTS, enabling seamless conversion between spoken and written language. An adaptive learning component is introduced, utilizing machine learning algorithms to generate personalized quizzes based on user interaction and performance, promoting effective language learning. By combining advanced natural language processing with interactive educational tools, this translation system serves both as a robust language translation solution and as an innovative platform for language acquisition, applicable in educational and cross-cultural communication contexts.